Pengaruh Sains dan Teknologi terhadap Pengembangan Kurikulum PAI dalam Pendidikan Abad 21 - Anisa Fitri; Amril M (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
This article discusses the influence of science and technology on the development of PAI curriculum. The urgency of the study of the impact of Science and Technology on PAI Curriculum development is to know and understanding that the evolution of curricula is heavily influenced by science and technology. This study uses the library research method, which uses reference sources such as books and articles in search of data sources. The results of the study conclude that among the factors that form the basis or even influence the development of curricula are science and technology. The development of curricula in education should have the ability to anticipate the impact of the era of globalization, which sends society without the basis of science, and in it there are IPTEK that become the main drivers in the change of systems much better. Plus, the fact that the world is facing the era of Industry 4.0. Besides, science and technology are so much needed for learning skills in the 21st century, especially in terms of information and communication technology literacy. Computer and literacy technology.